2009
DOI: 10.1097/jto.0b013e3181a97e31
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Vascular Endothelial Growth Factor Expression in Patients with Lung Cancer: A Systematic Review with Meta-Analysis

Abstract: VEGF overexpression indicates a poor prognosis for patients with NSCLC and SCLC; VEGFC and VEGFR3/flt-1 overexpression was not significantly correlated with survival for patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 72 publications
6
103
0
10
Order By: Relevance
“…Tumor growth and metastasis require angiogenesis, which is regulated by various factors, including the vascular endothelial growth factor (VEGF) (17). VEGF overexpression is an indicator of poor prognosis in patients with non-small and small cell lung cancer (18). Shimanuki et al measured the serum VEGF levels preoperatively in patients with non-small cell lung cancer and revealed a correlation with microvessel density in the resected tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor growth and metastasis require angiogenesis, which is regulated by various factors, including the vascular endothelial growth factor (VEGF) (17). VEGF overexpression is an indicator of poor prognosis in patients with non-small and small cell lung cancer (18). Shimanuki et al measured the serum VEGF levels preoperatively in patients with non-small cell lung cancer and revealed a correlation with microvessel density in the resected tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Confirming these results, in the previously mentioned study by Lucchi et al, VEGF levels were an independent adverse prognostic factor in the adjuvant setting (25). Additionally, Zhan et al performed a systematic review and meta-analysis of VEGF expression in lung cancer and again confirmed that VEGF is a prognostic factor in SCLC (32). Moreover, it has been demonstrated that SCLC cell lines express VEGFR2/3 receptors suggesting that the VEGF/VEGFR pathway is an autocrine growth regulator in SCLC (33).…”
Section: Angiogenesis In Sclcmentioning
confidence: 55%
“…In a recent meta-analysis of 5,386 NSCLC and SCLC patients, VEGF overexpression indicated poor survival for those with NSCLC histology, whereas VEGFR-3 expression did not affect prognosis (17).…”
Section: Discussionmentioning
confidence: 99%
“…There is plentiful literature regarding the association of angiogenic factors with disease prognosis (4,(14)(15)(16)(17)(18)(19)(20); however, only a few studies evaluate the role of such factors in predicting response to chemotherapy (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%